The Role of Capital Structure in Mediating the Effect of Liquidity on Profitability - Astina Tinus; Bambang Mahmudi; Enok Nurhayati (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The objective of this study is to assess the impact of the Current Ratio (CR) on the Net Profit Margin (NPM), with the Debt-to-Equity Ratio (DER) and Debt-to-Asset Ratio (DAR) serving as intervening variables. This research was conducted due to certain business phenomena that became the focal point of investigation, discrepancies between empirical data and existing theories, and gaps in previous studies that prompted the need for further exploration. This study employs a quantitative research approach, utilizing data collection techniques based on company financial reports through documentation methods. The population of this study comprises all companies listed and consistently included in the Business-27 Index on the Indonesia Stock Exchange (IDX) from 2013 to 2022. A total of 6 companies were selected as samples from the 27 companies available, using purposive sampling methods. Path analysis and the Sobel test were utilized as data analysis techniques in this research. The findings of this study indicate that the CR does not have a significant impact on NPM. However, CR has a negative and significant effect on both DER and DAR. Furthermore, DER and DAR do not have a significant influence on NPM. While DER cannot mediate the relationship between CR and NPM, DAR can mediate this relationship.